Quaternary intensification of spine epibiosis in the cidaroid echinoid Eucidaris: implications for anthropogenic impacts - Petsios, Elizabeth; Fuchs, Corinne E.; Kowalewski, Michal; Larson, Paul; Portell, Roger W.; Tyler, Carrie L. (Frontiers in Marine Science, 2025)
Echinoids are an integral part of present-day and ancient marine trophic webs, and they host a variety of mutualistic, commensalistic, and parasitic epibionts on their spines and test. Cidaroid echinoid (slate pencil urchins) spines in particular are commonly colonized by epizoans. Eucidaris in the western Atlantic and eastern Pacific today are notable for the frequency and intensity of calcifying, non-calcifying, and galling colonization on their spines. While moderate levels of spine colonization may provide camouflage and other benefits to the host, a high density of encrusters may instead reduce host fitness, and galling is invariably parasitic. Significant environmental changes in the equatorial and sub-equatorial western Atlantic and eastern Pacific necessitate a paleobiological approach to constrain the timing of changes in epibiosis intensity on Eucidaris. Here, we compare rates of spine colonization in present-day Eucidaris populations with ancestral Pliocene Eucidaris assemblages. We find that Pliocene spines show no evidence of parasitic galling, and significantly less evidence of epibiosis than their present-day descendants in both the Atlantic and Pacific. This holds true even after accounting for taphonomic processes that would preferentially erase evidence of non-calcifying colonization. We propose that the high intensity of colonization on present-day Eucidaris spines is a relatively recent development and may reflect human-induced habitat degradation in the region, underscoring the need for further investigation into this biotic interaction.